Implementation of four-quadrant DC Chopper for driver DC motor using Arduino - Ridwan, Ainul; Yuhendri, Muldi (Journal of Industrial Automation and Electrical Engineering, 2025)
This study aims to design and implement a DC motor control system using a four-quadrant DC chopper to enhance motor operation flexibility and efficiency. Conventional DC motor control methods often suffer from high starting currents and limited speed control capabilities. The proposed system utilizes an H-Bridge chopper circuit controlled by MOSFETs with Pulse Width Modulation (PWM) signals generated by an Arduino Mega 2560 and programmed through MATLAB Simulink. The four-quadrant chopper enables motor operation in forward motoring, forward braking, reverse motoring, and reverse braking modes. Experimental results demonstrate that the system effectively regulates motor speed and direction while minimizing excessive inrush current. The test results indicate a direct correlation between PWM duty cycles and output voltage, validating the system’s ability to provide precise motor control. Furthermore, the integration of regenerative breaking enhances energy efficiency. This study provides a robust solution for DC motor control applications requiring bidirectional operation and dynamic speed adjustments